A review on the detection methods of the resistant gene in Acinetobacter baumannii - Pavitra Manokaran; Suhaini Sudi; Moh Pak Yan; Mohd Khalizan Sabullah; Chee, Fuei Pien; Jualang Azlan Gansau; Zhihe, Qing; Goh, Lucky Poh Wah (Bentham Science Publishers B.V., 2025)
The rising prevalence of Multidrug-Resistant (MDR) Acinetobacter baumannii, particularly in hospital environments, has become a global health concern due to its capacity to cause severe infections and its resistance to conventional antibiotics. This article reviews the detection methods for the resistant genes, focusing on carbapenem-resistant A. baumannii (CRAB), where various phenotypic, molecular, and advanced diagnostic technologies, with particular attention to Fluorescence Resonance Energy Transfer (FRET) assays based on Quantum Dots (QDs) and Graphene Oxide (GO), are reviewed. These nanoparticle-based FRET assays show promising potential for rapid, sensitive, and multiplex detection of antibiotic resistance genes, offering significant improvements over traditional methods. In particular, integrating QDs and GO as donor-acceptor pairs in FRET allows real-time detection and high specificity of a key determinant of carbapenem resistance in A. baumannii. Adopting these advanced diagnostic tools could revolutionise infection control and management, providing timely and accurate diagnostics that are crucial in clinical settings.